The Importance of Explosive Energy on Mining Costs - John T. Day; Lex L. Udy; Mark L. Thomas (International Society of Explosives Engineers, 1987)
When we consider that the purpose of blasting is to fragment rock or ore so it can be subsequently handled and processed, we can see that the cost of blasting, in reality, affects all downstream steps of the mining (and in some cases) production processes. The productivity of all subsequent operations is influenced by the degree of fragmentation of the primary blast.